Tolong bantu jawab dong 🙂
Penjelasan dengan langkah-langkah:
No 1
x² + 4x – 12 = 0
x² + 6x – 2x – 12 = 0
x(x + 6) – 2(x + 6) = 0
(x + 6)(x – 2) = 0
x + 6 = 0 dan x – 2 = 0
x = -6 dan x = 2
No 2
x² + 6x + 5 = 0
x² + 5x + x + 5 = 0
x(x + 5) + 1(x + 5) = 0
(x + 5)(x + 1) = 0
x + 5 = 0 dan x + 1 = 0
x = -5 dan x = -1
No 3
5x² + 13x + 6 = 0
5x² + 10x + 3x + 6 = 0
5x(x + 2) + 3(x + 2) = 0
(x + 2)(5x + 3) = 0
x + 2 = 0 dan 5x + 3 = 0
x = -2 dan x = -3/5
Penjelasan dengan langkah-langkah:
maaf kalau salah jangan lupa jadikan jawaban terbaik ya (◠‿◕)